Practice-based lessons in photographic education: an alternative to photo image development / Dona Lowii Madon, Raziq Abdul Samat and Shafirah Shaari - Madon, Dona Lowii; Abdul Samat, Raziq; Shaari, Shafirah (Faculty of Art and Design, 2024)
The utilisation of contemporary photography technology facilitates rapid knowledge acquisition and enhancement of several aspects. Nevertheless, the fundamental process of picture-making needs to be adequately emphasised, resulting in a negligent approach and a lack of comprehension among students regarding the significance of generating high-quality images. This practice-based lesson aims to elucidate to students the fundamental relevance of picking picture image designs as a precursor to producing impactful photography. The chosen topic for creating artistic works is around nature and is centred on the Malacca campus. The PCT256 - Contemporary Photography Practice course selection at Universiti Teknologi MARA was based on its alignment with the initial approach, which involves creating artwork through various photographic processes. The subsequent topic, assessment analysis, will use the scoring rubric to assess the student's comprehension of the material. The fabrication of 58 pieces involved a total of 29 students. This essay will address the production process's various difficulties, problems, and challenges. The research findings indicate that students have a more significant potential for comprehending the process when they engage in iterative attempts to produce optimal outcomes.